A new Eulerian Iceberg module for climate studies - Erokhina, Olga; Mikolajewicz, Uwe (Journal of advances in modeling earth systems, 2024)
Icebergs modulate the effective location of freshwater input from ice sheets into the ocean and therefore play an important role for the climate, especially during times of increased ice discharge (e.g., Heinrich events). None of the models participating in the Paleo Modeling Intercomparison Project simulations of the Last Glacial Maximum or the last deglaciation included icebergs. Here, we present a newly developed dynamic/thermodynamic iceberg module that was specifically designed to be incorporated in climate models used for long-term climate simulations with interactive ice sheets. In contrast to the widely used Lagrangian iceberg models, it is formulated in an Eulerian framework. This simplifies coupling to ocean models and enhances computational efficiency for glacial climates. In a set of sensitivity experiments, where the module was implemented into an Earth System Model, we validate the model for present-day climate conditions and test its sensitivity to key parameters. Further, we investigate the effect of iceberg hosing on the Atlantic meridional overturning circulation (AMOC) as compared to traditional freshwater hosing. Varying the hosing rate slowly in time yields a good approximation of the hysteresis curve of the AMOC. We find that the sensitivity of the AMOC to iceberg hosing is stronger than to freshwater hosing in the same ocean point, but weaker as compared to a latitude belt forcing in the North Atlantic. This emphasizes the necessity to include interactive icebergs in long-term coupled climate simulations to realistically represent melt patterns and the response of the AMOC to freshwater input from melting ice sheets.
Zuerst veröffentlicht: 17. März 2024
Gesehen am 12.08.2024